Pengembangan Media Pembelajaran Scrapbook Digital Pada Materi IPAS di Sekolah Dasar - Rosyada, Amrina; Faisal, Faisal; Saputra, Agra Dwi; Nurlaeli, Nurlaeli; Syarifuddin, Ahmad (Limas PGMI, 2025)
This research aims to produce Digital Scrapbook learning media and evaluate the validity, practicality and effectiveness in learning IPAS class V at SDN 159 Palembang. Using the ADDIE development model by Dick and Carey, this research involves the stages of Analysis, design, development, implementation, and evaluation. The test subjects were one teacher and 25 students. The instruments used include validation sheets for material, media and language experts, as well as practical sheets for teachers and students. With effectiveness measured through formative tests. This research was conducted from February 7 to 15, 2025. The results of the validity study showed that the Digital Scrapbook obtained an excellent average score: 92% from media experts (very valid), 76% from linguists (valid), and 98.46% from material experts (very valid). Positive responses from teachers reached 92.85% (very practical), while students reached 95.54% (very practical). The level of effectiveness was obtained through the pretest-posttest, with an N-Gain Score value of 0.6246 < 0.7 (Quite effective) These findings indicate that the Digital Scrapbook learning media is feasible, practical and effective enough to be used in IPAS learning. As a follow-up. Digital Scrapbook will be applied in IPAS learning and teachers will be directed to maximize its utilization. Further research is recommended in other schools to increase the level of effectiveness of the media.